Governments and companies must address climate and governance risks when petroleum assets change hands - Nicola Woodroffe; Erica Westenberg (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2023)
When MNEs with strong environmental and governance commitments sell petroleum assets to companies with weaker commitments, climate and governance risks may increase. Governments and companies should revisit approaches to petroleum legal frameworks and update company and investor social responsibility to ensure standards do not slip when projects change hands.
Keywords: 330